2021
DOI: 10.1088/1748-0221/16/03/p03033
|View full text |Cite
|
Sign up to set email alerts
|

Towards soft x-ray fluorescence measurements in the laboratory using a laser-produced plasma source and a complementary metal-oxide semiconductor detector

Abstract: With the advent of commercially available CMOS technology suitable for direct detection of photons in the soft X-ray range, new possibilities are opening up for the improvement and optimization of experiments requiring energy discrimination capabilities in this energy range. SDDs are widely used as energy-dispersive detectors, but they cannot be used with pulsed sources due to the overwhelming temporal photon density. Wavelength-dispersive solutions offer unmatched energy resolution, but suffer from low detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…It has been shown that these sensors dramatically increase the full-frame acquisition speed (48 Hz for the standard gain and 24 Hz for the HDR mode) compared to the commercial Back-Side-Illuminated Charge-Coupled Device (CCD-BSI) routinely used at soft X-ray facilities. The first utilization of this device opened up perspectives for soft X-ray ptychography (Mille et al, 2022), soft X-ray scattering techniques (Desjardins et al, 2020;Marras et al, 2021) and other applications, such as soft X-ray fluorescence (Staeck et al, 2021). Another obvious application concerns the implementation of such a class of detectors at ultra-short X-ray sources (laser-based X-ray source or free-electron laser), where the low frame rate of the standard commercially available CCD-BSI (see, for example, Vodungbo et al, 2012;Wang et al, 2012) limits the time of data collection.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that these sensors dramatically increase the full-frame acquisition speed (48 Hz for the standard gain and 24 Hz for the HDR mode) compared to the commercial Back-Side-Illuminated Charge-Coupled Device (CCD-BSI) routinely used at soft X-ray facilities. The first utilization of this device opened up perspectives for soft X-ray ptychography (Mille et al, 2022), soft X-ray scattering techniques (Desjardins et al, 2020;Marras et al, 2021) and other applications, such as soft X-ray fluorescence (Staeck et al, 2021). Another obvious application concerns the implementation of such a class of detectors at ultra-short X-ray sources (laser-based X-ray source or free-electron laser), where the low frame rate of the standard commercially available CCD-BSI (see, for example, Vodungbo et al, 2012;Wang et al, 2012) limits the time of data collection.…”
Section: Introductionmentioning
confidence: 99%
“…Since this X-ray tube is commercially available, it is easy to utilize in a purpose-built setup. The currently used Tucsen Dhyana 95 detector also leaves some room for improvement regarding the quantum efficiency below 1 keV [ 25 ]. Newer models with improved quantum efficiency could help reduce the measurement time even further [ 24 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The beamline uses a plane grating mirror monochromator and the beam size is 1 mm × 1 mm. The detector used is a Tucsen Dhyana 95 CMOS detector [ 25 ]. This detector was adapted for the use in the soft X-ray range [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations